Relationship of Friend/Parent Exercise Participation Levels and Adolescents' Exercise Intention/Behavior as Moderated by Action Control. Issue 2 (April 2020) - Lee, Keunchul; Lee, Kanghun
This study investigated the role of action control in the relationship between friend and parent exercise participation levels with adolescents' exercise intention and behavior, based on the theory of planned behavior. Data were collected from 740 Korean adolescents through questionnaires that assessed the exercise participation level of these participants' parents and friends, and the adolescent participants' personal exercise intention, exercise behavior, action control, and exercise constraints. The results showed that the exercise participation level of friends, but not of parents, mediated the adolescents' exercise behavior through their exercise intention. This relationship was magnified by higher levels of the adolescents' action control.